Marx’s Social Capital Reproduction Model: A Technical Supplement - Xian Zhang (World Review of Political Economy, 2021)
The study on how Marx created the theory of social capital reproduction shows that this theory ranks among his original contributions to economics. In this theory, Marx’s analysis of Department II and the exchange relation reveals the conditions that capitalist reproduction must follow if it is to proceed smoothly. The fully indirect exchange process indicates that the capitalists’ individual consumption preferences, and changes in these preferences, are factors not only in determining capital accumulation but also in destroying the proportional relations of reproduction. Although Marx proposed the decomposition of Department II and made a theoretical analysis of the law of the simple reproduction of social capital after decomposition, he did not construct a complete model or make the same decomposition of the two major departments in the analysis of the reproduction of social capital on an extended scale. As a result, it is necessary to develop a technical supplement on the basis of Marx’s department decomposition principle, so as to cast light on the correctness of his theory of social capital reproduction and on the inevitability of capitalist reproduction crises.